Evaluation of twenty‐two rapid antigen detection tests in the diagnosis of Equine Influenza caused by viruses of H3N8 subtype. Issue 2 (1st February 2016) - Yamanaka, Takashi; Nemoto, Manabu; Bannai, Hiroshi; Tsujimura, Koji; Kondo, Takashi; Matsumura, Tomio; Gildea, Sarah; Cullinane, Ann
Abstract : Background: Equine influenza (EI) is a highly contagious disease caused by viruses of the H3N8 subtype. The rapid diagnosis of EI is essential to reduce the disease spread. Many rapid antigen detection (RAD) tests for diagnosing human influenza are available, but their ability to diagnose EI has not been systematically evaluated. Objectives: The aim of this study was to compare the performance of 22 RAD tests in the diagnosis of EI. Methods: The 22 RAD tests were performed on fivefold serial dilutions of EI virus to determine their detection limits. The four most sensitive RAD tests (ImmunoAce Flu, BD Flu examan, Quick chaser Flu A, B and ESPLINE Influenza A&B‐N) were further evaluated using nasopharyngeal samples collected from experimentally infected and naturally infected horses. The results were compared to those obtained using molecular tests. Results: The detection limits of the 22 RAD tests varied hugely. Even the four RAD tests showing the best sensitivity were 125‐fold less sensitive than the molecular techniques. The duration of virus detection in the experimentally infected horses was shorter using the RAD tests than using the molecular techniques. The RAD tests detected between 27% and 73% of real‐time RT‐PCR‐positive samples from naturally infected horses. Conclusions: The study demonstrated the importance of choosing the right RAD tests as only three of 22 were fit for diagnosing EI. It was also indicated that even RAD tests with the highest sensitivity serve only as an adjunct to molecular tests because of the potential for false‐negative results.